Reliability and validity of change-of-direction speed tests for junior basketball players - Selakovic, N.; Krneta, Z. (Facta Universitatis: Series Physical Education and Sport, 2020)
The main goal of this study was to determine the reliability and validity of change-of-direction speed (CODS) tests for junior basketball players and to test the differences between the positions of players on the team. On a sample of 66 junior basketball players (18.2±3.18 years), the CODS was tested using the following tests: the Lane Agility Test (LAT), Zigzag Agility Test (ZAT), Agility T-test and Modified Agility T-test. Body height and body mass were used as control variables. a-Cronbach's coefficient was calculated to determine the reliability and internal consistency of the measurements, as well as the average correlation between the trials of each test. The difference between groups of players was tested by MANCOVA. CODS tests showed good to high reliability (interclass correlations ranged from 0.83-0.93 with a variability of 4.4% to 6.4% for the entire sample). The first principal component was determined, which included 83% of the total variance of the analyzed variables. Very high coefficients of internal validity of all the applied tests (0.93-0.98) were obtained on the common subject of defined measurements. Significant differences were found between groups of players by position in favor of outside players (guards) on two tests LAT and ZAT (F=18.023; 8.559 and p=0.005) with control of the influence of body height and body mass. All tests can be rated as reliable and valid for junior basketball players. LAT proved to be the most suitable for assessing the CODS in young basketball players, with the best discrimination of players by position on the team.